The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/373608
|View full text |Cite
|
Sign up to set email alerts
|

Observations of TCRVβ Gene Expression in Rats with Dampness Syndrome

Abstract: Environmental dampness is one factor which can cause human diseases. The effects of exposure to humidity on human immune function are diverse and numerous. In the theory of traditional Chinese medicine (TCM), dampness is defined as one of the major pathogenic factors in the human body. It is divided into “external dampness” and “internal dampness.” However the molecular mechanism leading to humidity-induced immunosuppression is obscure. In the present study, we investigated the expression of the T-cell antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Interestingly, the majority of patients with cancer cachexia have been diagnosed with SD in China ( Sun et al, 2016a ; Zhang et al, 2020 ). According to the literature, SD may lead to dysfunction in T cell recognition by disordering the expression of TCRVβ in rats ( Chen et al, 2014 ). In addition, another study reported that immunoregulatory traditional Chinese medicine is beneficial to liver cancer and induces cell apoptosis through the Caspase-3/PARP signaling pathway ( Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the majority of patients with cancer cachexia have been diagnosed with SD in China ( Sun et al, 2016a ; Zhang et al, 2020 ). According to the literature, SD may lead to dysfunction in T cell recognition by disordering the expression of TCRVβ in rats ( Chen et al, 2014 ). In addition, another study reported that immunoregulatory traditional Chinese medicine is beneficial to liver cancer and induces cell apoptosis through the Caspase-3/PARP signaling pathway ( Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the theory of TCM, HCC can be referred to as the disease “abdominal dropsy,” which is mainly caused by “external dampness” and “internal dampness.” Therefore, the therapeutic strategy for HCC in TCM is to resolve the “dampness.” At the same time, the “dampness” in TCM has been verified to be correlated with the obstruction of immunological recognition function [ 12 ]. As one of the representative herbal medicines in resolving dampness, Yinchen has been used in liver diseases in TCM for many years.…”
Section: Discussionmentioning
confidence: 99%
“…It is the key point to improve the “internal dampness” microenvironment of HCC patients. Based on the theory of TCM, Yinchen aims at the liver and can ameliorate the “internal dampness.” Meanwhile, it has been reported that the obstruction of immunological recognition function might be caused by “internal dampness” [ 12 ]. Consequently, we speculated that Yinchen may have an effect on HCC through the immunologic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its importance and complexity, researchers have focused on the properties of the spleen. It is well documented that the spleen is not only an anatomical concept, but is also associated with the digestive system (29,30) in particular, in addition to the immune (31), circulatory (32) and endocrine systems (33). Previously, Huang et al (14,15) suggested that the spleen was involved in the pharmacokinetics hypothesis, which assumes that the spleen is responsible for the absorption, distribution, metabolism and excretion of drugs.…”
Section: Discussionmentioning
confidence: 99%